ANALYSIS OF THE REALIZATION OF DOMESTIC MARKET OBLIGATION POLICY ON NATIONAL ENERGY SECURITY INDEPENDENCE - Oxaria Silviana Devi; Suryaningsum, Sri; Sutoyo (Count : Journal of Accounting, Business and Management, 2024)
Prior to the implementation of the Domestic Market Obligation (DMO), coal mining companies preferred to sell coal to international users rather than use it for domestic utilization. A possible explanation for this is that the revenue that coal mining companies can earn internationally is more than domestically and market instability further limits coal supply options. This research aims to evaluate the effectiveness of the coal DMO in the context of national energy security in Indonesia during 2020-2023. It seeks to analyze the extent to which the policy has been realized and its implications for the country's energy landscape. Employing a post-positivism approach, this research utilizes qualitative data collection methods to gather insights on the implementation of the coal DMO policy. The study examines relevant documents and policy reports in the energy sector to assess the realization and impact of the Coal DMO. The findings show that the realization of the Coal DMO has not been optimal because the target was only achieved in 2022 and 2023. This is due to several factors, namely not all coal specifications are suitable for domestic power plants, there is a price disparity between domestic prices and international prices and the fines or compensation implemented are not sufficient to form sustainable compliance for coal mining entrepreneurs. The conclusions of this study contribute to the existing literature on energy policy and national security. It is also useful for policy makers, energy stakeholders and researchers interested in the dynamics of energy governance and security in Indonesia.